Use of inert gas-enriched atmospheres and post-packaging irradiation in shelf-life extension of watercress - Pinela, José (2016)
Watercress (Nasturtium officinale R. Br.) is a semi-aquatic plant of the Brassicaceae family highly appreciated in the Mediterranean cuisine. It features sharp, peppery and slightly tangy taste and contains health-promoting phytochemicals. Its consumption as a fresh-cut product has increased in recent years, as well as the global market of minimally processed vegetables. This demand is driven by the growing interest in the role of food in promoting the human health and wellbeing and to meet consumer needs for fresh-like and more convenient foods. Due to the reduced shelf-life of this plant, the suitability of inert gas-enriched atmospheres and ionizing irradiation for preserving visual, nutritional and functional quality attributes during cold storage was studied. Watercress samples were gathered in the Northeast region of Portugal, rinsed in tap water and a portion was immediately analyzed (non-stored control). The remaining fresh material was packaged in polyethylene bags under N2- and Ar-enriched atmospheres, conventional atmosphere (air) and vacuum (no atmosphere). Samples under conventional atmosphere were irradiated at 1, 2 and 5 kGy of gamma-rays (predicted doses) in a 60Co experimental chamber. A non-irradiated control followed all the experiment. Then, all packaged samples were stored at 4 ºC for 7 days. The studied quality parameters included the colour that was measured with a Konica Minolta colorimeter, and total soluble solids and pH determined in squeezed juice. The proximate composition (moisture, proteins, fat, ash, carbohydrates and energy) was evaluated using the AOA C procedures. Organic acids, free sugars, fatty acids and tocopherols were analyzed by chromatographic techniques. Samples were also evaluated for its DPPH• scavenging activity, reducing power, and lipid peroxidation inhibition capacity trough the inhibition of the β-carotene bleaching and thiobarbituric acid reactive substances (TBAR S) formation. Differences among treatments were analyzed using the one-way analysis of variance (ANO VA) and a linear discriminant analysis (LDA ) was used to evaluate the effects on the overall postharvest quality. After evaluating the effect on the individual quality parameters, the LDA revealed that the Ar-enriched atmosphere and the irradiation at 2 kGy were suitable processing choices for preserving the integrity of the non-stored control samples during cold storage. Thus, these non-thermal treatments were highlighted for shelf-life extension of fresh-cut watercress.